Estratégia de manutenção baseada na confiabilidade sistêmica em linhas de produção: estudo na Indústria Metal-Mecânica - Pinho, Bruno (Universidade do Vale do Rio dos Sinos, 2019)
The objective of this dissertation is to develop a method to define the strategy of maintenance of a metal-mechanic company of the forging sector. The maintenance strategies for thirteen machines were defined for a forging line and the raw material cutting sector. In the forging line, critical machines were identified by company identification and bottleneck analysis, applying the FMEA to identify failure modes. The research methodology is quantitative modeling and an exploratory research for the qualitative approach. The technique of quantitative research is the probabilistic modeling of the time between failures and the time for the repair for the machines and the mean time between failures for the system. The machines in the sector of cut are arranged in parallel, those of the forging line in series. Six machines are in the infant mortality period, which requires a corrective maintenance strategy. Seven machines are in the maturity period, which requires the predictive maintenance strategy. The production system was evaluated according to the diameter of the steel to be processed. The productive system that presented the best average time between failures was to produce items whose steel is Ø64mm to Ø120mm, 14.39h. Already the greater general availability of the system is for the production of items whose steel is of Ø35mm to Ø63mm, 90,63%. The definition of the machines for the application of the FMEA in the forging line occurred through the analysis of the line bottleneck and the company's indication, a machine that does not have backup, the hydraulic hammer and the induction furnace. In the hydraulic hammer, the most dangerous fault modes were found in the hydraulic control valves for the pilot pneumatic valve and in the electric drive system for the failure of the electric pedal. In the induction furnace the failure mode in the heating station was highlighted. The analysis of failure modes and their effects made possible improvements in the maintenance processes of the two machines identified as critical in the forging line. The realization of FMEA made it possible to complement the adequate maintenance strategies for the analyzed machines, proposing specific practices of preventive maintenance.
Keywords: Estratégia de manutenção; Confiabilidade; Mantenabilidade; FMEA; Maintenance strategy; Reliability; Maintenanceability; FMEA; ACCNPQ::Engenharias::Engenharia de Produção